Analisis Perputaran Modal Kerja Dan Perputaran Total Aset Terhadap Basic Earning Power (BEP) - ., Suhaeni; Marpaung, Annaria Magdalena (LPPM Institut Bisnis dan Informatika Kesatuan, 2017)
Working capital in a company is very important because it pays the company’s all current liabilities, its sources can be derived from the results of the company's operations and sales profits. The higher working capital turnover, the smaller funds that are embedded in working capital to achieve sales, thus showing that the company is efficient in the use of working capital. Basic earning power describes the company's effectiveness in utilizing all sources of funds, which shows the economic profitability of the company. The purpose of this study was to determine and analyze whether or not there are relationships between working capital turnover and asset turnover total of the basic earning power. The study was conducted at PT Indofood Sukses Makmur, Tbk and PT Mayora Indah Tbk. using the simultaneous linear regression analysis as the tool for the analytical method. The research resulted that for the case of PT Indofood Sukses Makmur there is a significant relationship between working capital turnover and total asset turnover on the basic earning power. As for PT Mayora Indah Tbk. author did not find a relationship between working capital turnover and total asset turnover total on the basic earning power due the result of SPSS being not significant.